Optimasi Hidroksipropil Metilselulosa dan Mentol pada Sediaan Gel Dispersi Padat Ibuprofen–Polietilenglikol dengan Metode Desain Faktorial (Optimization of Hydroxypropyl Methyl Cellulose and Menthol in Ibuprofen Gel Solid Dispersion-Polyethyleneglycol usi - Maharani Dwi Pratiwi; Dwi Nurahmanto; Viddy Agustian Rosyidi (Pustaka Kesehatan, 2017)
Ibuprofen is included in non-steroidal anti-inflammatory drug (NSAID) which is used for the treatments of arthritis and inflammation. Ibuprofen gel is an effective approach evading ibuprofen's side effect in GI tract and first pass effect. The aims of this study was to determine the effect of HPMC and menthol combination on viscosity, penetration flux and to obtain the optimum formula.The gel evaluations were organoleptic testing, pH, viscosity, spreadibility test, assay of ibuprofen gel, and in vitro penetration rate. In vitro penetration testing used the paddle type dissolution tester. Furthermore ibuprofen which penetrated through rat skin were analyzed by UV-Vis spectrophotometer. Ibuprofen gel were prepared into four formulas based on factorial design and the data were analyzed using design expert trial 9.0.3. The viscosity testing of F1, Fa, Fb, and Fab were 183.30 ± 14.433,261.67 ± 16.07, 158.33 ± 7.637, and 310.0 ± 13.23 dPa.s. The in vitro penetration rate of F1, Fa, Fb, and Fab were 0.7225, 0.6716, 1.5587 And 1.0702 µg/cm2.minutes. It can be concluded that Fb has the optimum formula. Keyword: optimization, HPMC, menthol, factorial design